Habituation of Krama Inggil Language in Forming Children's Character and Morals - Khoirun Nisa; Suyadi Suyadi; Desika Putri Mardiani (LP3M STAI MA'ARIF MAGETAN, 2023)
The purpose of this research is to find out how parents and the environmentapply habituation which aims to shape the character and morals of children in theKencong Hamlet, Jambi Village, Baron District, Nganjuk Regency. By using a casestudy qualitative research method and data collection techniques of observation,interviews and documentation the results of this study are that parents apply kramainggil language from infancy, according to parents besides local wisdom it ismaintained, krama inggil language makes children's personalities more politeconsidering that the Javanese language has rules that must be obeyed. Success inimplementing krama inggil language habituation is also influenced by the conduciveenvironment in which all the people in the hamlet have kinship relations